Development and Application of a Platform for Multidimensional Urban Earthquake Impact Simulation - Hsu, Chih-Hao; Ke, Siao-Syun; Wu, Tzu-Hsiu (Frontiers in Built Environment, 2022)
Earthquakes can be devastating to cities. Therefore, accurate and efficient simulation of the potential seismic damage to buildings has become an indispensable part of worldwide efforts to mitigate earthquake hazards. Precise simulation results can highlight potential seismic damage and serve as a reference in urban development and for planning post-earthquake rescue operations. In urban areas, simulation of the structural dynamic response during an earthquake is key for planning an appropriate emergency response. Multidimensional visualization of the effects of earthquakes is a popular technique in current earthquake simulation research. In the present study, a dynamic multidimensional simulation method was developed for analyzing the impact of an earthquake on buildings. This method involved conducting three-dimensional (3D) dynamic analysis of data from a seismic capacity database. Polygonal models and seismic capacity data were used in a high-performance computing process to calculate the seismic response of each building in an urban environment. On the basis of the calculations, a platform was developed for multidimensional urban earthquake impact simulation (MDUES). The developed MDUES platform enables analysis of the impact of long-period earthquakes, simulation of the 3D seismic responses of buildings, and visualization of the disaster risk and earthquake impact in a specified area. In summary, simulation of structural seismic responses in an urban setting necessitates a careful examination of the characteristics of ground and building motion, and the results of this simulation can provide a crucial reference for city planning, post-earthquake rescue operations, and seismic damage assessments.